(untitled) (Journal of Pakistan Orthopaedic Association, 2024)
Objective: The objective of this study was to evaluate the radiological outcomes and complication rates associated with the use of conventional growing rods in patients with EOS at Gourki Trust Teaching Hospitals, Lahore. Methodology: This retrospective cohort study included patients with EOS who were treated with single or double conventional growing rods between January 2017 and June 2023. Exclusion criteria were the use of magnetic growing rods and active apex correction techniques. Data on demographic, clinical, and radiological parameters were collected and analyzed using SPSS version 23. The study focused on outcomes such as COBB’s angle, T1 to S1 height, T1 to T12 height, apical vertebral translation, and thoracic kyphosis. Complication rates were also assessed. Results: A total of 32 patients (mean age 8.2 ± 1.3 years; 46.9% male, 53.1% female) were included. Of these, 34.4% had congenital scoliosis, and 65.6% had idiopathic scoliosis. Double rods were used in 87.5% of cases, while 12.5% had single rods. Postoperative radiological assessments indicated significant improvements in COBB’s angle, T1 to S1 height, T1 to T12 height, apical vertebral translation, and thoracic kyphosis. Complications occurred in 15.6% of cases, all of which involved double rod implants. Notably, 100% of single rod cases had no complications compared to 82.14% of double rod cases. Conclusion: Conventional growing rods effectively improve spinal alignment and growth in patients with EOS. However, double rod implants are associated with a higher complication rate compared to single rod implants.